A Preliminary Survey of Knowledge and Expectations on renewable Energy Among Malaysian University Accounting, Business and Economics students - Jainurin Justine; Mohd Allif Anwar Abu Bakar; Mohd Rizwan Abd Majid; Rostika Petrus Boroh (Universiti Malaysia Sabah, 2019)
Present students are future business and government leaders. As such, it is important to examine their knowledge and expectations regarding sustainable renewable energy. A questionnaire survey was carried involving a total of 207 students in accounting, business and economics fields in a Malaysian university. While a majority of the students answered correctly on questions related to renewable energy knowledge, there are those who did not. Accordingly, only 41.5% of respondents indicated their level of knowledge in renewable energy to be good or better. For expectations, most respondents agreed for countries to produce and utilize both renewable and nonrenewable sources of energy, but a significant percentage (39%) disagreed on building nuclear plants. A majority of the students also indicated willingness to pay for clean energy and renewable energy at home. The results of this research can be used by stakeholders in improving students’ knowledge and exposure to renewable energy through changes in the curriculum to include topics and assignments related to renewable energy or incorporating activities related to renewable energy in the campus environment.